The Effect of Schleichera oleosa L. on HbA1c Levels in Alloxan-Induced Rats - Awaluddin, Akbar; Zulkifli AS, Andi; Burhan, Asril; Awaluddin, Nurhikma; Amir, Hamka (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2022)
Diabetes mellitus is a chronic disease that occurs due to the failure of the pancreas to produce sufficient insulin, or the body cannot use the insulin it makes effectively. The HbA1c (glycated hemoglobin) levels show an alteration in blood glucose levels in people with diabetes. As a traditional medicine, the kesambi plant ( Schleichera oleosa L.) can improve diabetic people's health due to its secondary compounds, such as alkaloids, flavonoids, tannins, steroids, and phenolic compounds, besides several empirically proven as antiulcer, anticancer, and antimicrobial effects. The study aimed to determine the effect of the ethanol extract of Kesambi leaves on HbA1c levels in alloxan-induced rats. This research used a posttest-only design method, using 18 rats divided into six groups of mice and induced by alloxan 150 mg/kg in intraperitoneal with the division of groups: group I without treatment; group II alloxan + Na CMC; group III alloxan + glibenclamide; groups IV, V, and VI, given alloxan + kesambi leaf extract 200, 400, and 600 mg/kg BW, respectively. All treatments were given orally for 23 days. HbA1c values were measured on day 24 using the Afinion HbA1c. The data obtained were analyzed using the method of comparing the measurement results of each group against the control group. The results showed that the 200, 400, and 600 mg extracts affected HbA1c levels with successive values of 5.47%, 5.37%, and 5.47% compared to the control group, namely 5.10%. This study concluded that giving kesambi leaf ethanol extract can affect HbA1c levels.